Determinants of e-Money User Behavior Based on the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 Model Mediated by Behavioral Intentions - Irma Christiana; Linzzy Pratami Putri (Jurnal Bisnis dan Manajemen, 2024)
This study aimed to investigate the factors influencing UTAUT 2-based e-money user behavior, mediated by behavioral intentions. Data were collected through online questionnaires distributed via Google Forms. The research variables comprised performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit as independent variables, with user behavior as the dependent variable and behavioral intention as a mediating variable. Participants were selected using purposive sampling techniques. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS3 software. Hypothesis testing revealed that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and price value did not significantly influence e-money usage intention. Additionally, facilitating conditions did not significantly impact e-money user behavior. However, habit was found to significantly influence both intention to use and behavior of e-money users. Furthermore, the intention to use e-money mediated the relationship between performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and user behavior